Harmonisation of Criminal Provisions on Environmental Protection and Management in The Ordinance of Sustainable Environmental Maintenance - Trisna Agus Brata; Imam Syafa’i (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research will discuss the development of environmental problems that from time to time are getting worse as if not balanced with adequate law enforcement, even though all laws and regulations have been made. Criminal law enforcement is closely related to the ability of the apparatus and citizens' compliance with the laws and regulations that govern it. Related to this, as stated in Article 95 paragraph (1) of Law No. 32/2009 on Environmental Protection and Management, in the context of law enforcement against perpetrators of environmental criminal offences, integrated law enforcement can be carried out between Civil Servant Investigators (PPNS), police institutions, and prosecutorial institutions under the coordination of the relevant Minister. Thus, environmental law enforcement is an effort to achieve and realise the adherence to the provisions in generally applicable legal provisions, namely laws and regulations governing the environment.